Misbehaving Proteins Protein (Mis)Folding, Aggregation, and Stability - Murphy, Regina; Tsai, Amos (Springer New York : Imprint: Springer, 2006)
Misfoldedaggregatedproteinoncewasconsideredasinterestingasyesterday'strash-a bothersome by-product of important and productive activities, to be disposed of and forgotten as quickly as possible. Yesterday's trash has become today's focus of cons- erable scienti?c interest for at least two reasons: (1) protein aggregates are at the core of a number of chronic degenerative diseases such as Alzheimer's disease, and (2) - gregation poses signi?cant obstacles to the manufacture of safe, ef?cacious, and stable protein products. As interest in protein misfolding, aggregation, and stability has soared beyond the core group of traditional protein-folding scientists, and as substantial scienti?c progress in understanding and controlling protein misfolding has been achieved, the need to summarize the state of the art became manifest. Although there are many excellent texts and edited collections on protein structure and folding, these volumes tend to relegate protein misfolding and aggregation to a minor role. Review articles and books focused on the biological role of protein aggregates in diseases have been published recently. Misbehaving Proteins: Protein (Mis)folding, Aggregation, and Stability differs from theseotherrecenteffortsinitsemphasisonfundamentalcomputationalandexperimental studies and in its linkage of disparate consequences of protein misfolding (e.g., from clinical manifestations to manufacturing headaches) to their common causes.